2016
DOI: 10.1007/s10903-016-0451-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity Differ by Sex and Country of Birth Among Mexican-Heritage Youth

Abstract: Barriers to physical activity (PA) may be experienced differently by sex and country of birth. We examine psychosocial correlates of PA in four groups based on sex (boy/girl) and country of birth (Mexico/United States (U.S.). 1,154 Mexican heritage adolescents residing in Houston, Texas provided psychosocial data in 2008–09 and PA (number of days per week active for at least 60 minutes) in 2010–11 (N=1,001). Poisson regression models were fitted for each groups. Among boys, English language preference (pUS-bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(31 reference statements)
0
6
0
6
Order By: Relevance
“…Furthermore, although PA seems to reduce depression and anxiety symptoms, little attention has been given to examining whether gender (i.e., male-female) influences psychological health outcomes. In a recent study (Wilkinson et al, 2017), anxiety related to body image was shown to be lower for American-born and Mexican-born females who engaged in more PA than for those who were less engaged in PA. However, this relationship was different for the males in the study.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, although PA seems to reduce depression and anxiety symptoms, little attention has been given to examining whether gender (i.e., male-female) influences psychological health outcomes. In a recent study (Wilkinson et al, 2017), anxiety related to body image was shown to be lower for American-born and Mexican-born females who engaged in more PA than for those who were less engaged in PA. However, this relationship was different for the males in the study.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, given that gender has been proposed to moderate the relationship between PA and some psychological problems (i.e. McMahon et al, 2017;Sun et al, 2014;Wilkinson et al, 2017), we performed all analyses stratified by gender. We hypothesized that higher MVPA would be more protective against psychological health in boys than in girls.…”
Section: Introductionmentioning
confidence: 99%
“…Además, los niveles de incertidumbre aumentan ya que gran parte de los adolescentes mexicanos afirman no tener intención futura de practicar AFD en su tiempo libre (Baños, 2020). En esta línea, aumenta la diferencia en función del género, ya que las chicas se muestran menos activas y la AFD que practican es de menor intensidad (Cocca, Chmelik, Cocca, Espino, & Rodenas, 2017;Wilkinson, Miller, Koehly, Daniel & Forman, 2017). Por lo que el panorama en los jóvenes mexicanos es alarmante.…”
Section: Introductionunclassified
“…the older the person, the less physical condition, which denotes non-linearity (Bauman et al, 2009;Palomino et al, 2017;Prieto Benavidez et al, 2015;Delgado -Floody et al, 2019), those that show how it is in adulthood where physical activity practice increases again and physical condition improves (Humphreys and Ruseski 2010) those that establish how BMI is closely related to diet, physical activity practice and parents' schooling (Bucco-dos Santos,& Zubiaur-Gonzales 2013;Díaz-Martínez et al, 2013;Cubidos de Carrillo, 2015;Zurita-Ortega et al, 2018;), who propose how sleep restriction is a risk factor associated with the presence of obesity (Duran et al, 2012;Reverter-Masia et al, 2017), those who mention the importance of staying active, i.e., engaging in physical activity, physical exercise and sport, and their relationship with different social and cultural aspects (Alvarez, et al, 2020) those that show that schoolchildren with physically active parents are more inclined to practice sport (Zurita-Ortega, 2018, Solis-Urra et al, 2019. Based on the above associations, it was found that the social determinants of health that predict healthy physical condition are BMI, living with the father, number of meals he consumes per day, being a beneficiary at the school restaurant and hours he sleeps at night, which are modifiable, an aspect that invites to continue insisting on processes of construction and implementation of effective nutrition programs, lifestyles and social coexistence that help improve the physical condition of schoolchildren as well as other studies suggest (Wilkinson, 2016 ;Carulla, et al, 2019;Ochoa-Martínez et al ,. 2018).…”
Section: Discussionmentioning
confidence: 88%